Glycogen synthase kinase 3 induces multilineage maturation of human pluripotent stem cell-derived lung progenitors in 3D culture - Carvalho, Ana Luisa Rodrigues Toste de (2019)
Although strategies for directed differentiation of human pluripotent stem cells (hPSCs) into lung and airway have been established, terminal maturation of the cells remains a vexing problem. We show here that in collagen I 3D cultures in the absence of glycogen synthase kinase 3 (GSK3) inhibition, hPSC-derived lung progenitors (LPs) undergo multilineage maturation into proximal cells, type I alveolar epithelial cells and morphologically mature type II cells. Enhanced cell cycling, one of the signaling outputs of GSK3 inhibition, plays a role in the maturation-inhibiting effect of GSK3 inhibition. Using this model, we show NOTCH signaling induced a distal cell fate at the expense of a proximal and ciliated cell fate, whereas WNT signaling promoted a proximal club cell fate, thus implicating both signaling pathways in proximodistal specification in human lung development. These findings establish an approach to achieve multilineage maturation of lung and airway cells from hPSCs, demonstrate a pivotal role of GSK3 in the maturation of lung progenitors and provide novel insight into proximodistal specification during human lung development.